Recognition and Development of Communication Science in the Netherlands - Hemels, Joan (2018)
Emphasizing the leading role of Amsterdam and Nijmegen Universities, the article summarizes the main stages and points out the major protagonists of the process of academic institutionalization of communication studies in the Netherlands since the 1970s. At first it reports the contribution of older researchers (Stappers, Brouwer and van der Ban) in the transition that academically represented the growing interest in specializing the study of the subject at that time.  In a second moment, it highlights the local role permormed by the British researcher Denis McQuail,  responsible for the international projection of the new field of studies, occurred during the 1980s. In conclusion, the article presents a quick overview of the most recent institutional situation and its main lines of research.